Effect of ethanol extract of Erythrina fusca Lour (cangkring) leaves on suppression of cyclooxygenase-2 expression in raji cell line - Zullies Ikawati; Agung Endro Nugroho; Winda Werdhinindah (Indonesian Journal of Pharmacy, 2006)
COX-2. COX-2 is expressed highly in inflammation and cancer cells. The effect of ethanol extract of Erythrina fusca Lour (cangkring) toward suppression of COX-2 expression in Raji cells was studied using immunocytochemistry method. This research showed that ethanol extract of E. fusca Lour leaves on concentration of 250,0; 125,0; dan 62,50 μg/mL was able to suppress the COX-2 expression significantly in comparison to control, with the inhibition of 70,19 ± 2,14 %; 44,69 ± 1,62 %; and 23,25 ± 2,21 %.Key words: COX-2 expression, anti-inflammation, anti cancer, Raji cells, ethanol extract of E. fusca leaves, immunocytochemistry